Seroprevalence of Toxoplasma gondii and Neospora spp. in equids from three municipalities in Pará, Brazil - Norlander, Emma (2014)
This study presents a survey of the seroprevalence of Toxoplasma gondii and Neospora spp. in equids in three municipalities in Pará, a Brazilian state with the Amazonian rainforest and the Amazon River as dominating features. Toxoplasma gondii and Neospora spp. are two closely related parasitic protozoans not separated as different genera until 1988. Neospora spp. includes two species, N. caninum and N. hughesi, that are impossible to distinguish between based solely on serology. Seroprevalence in previous studies from other areas of Brazil has presented a prevalence ranging from 5.9% to 43.2% for T. gondii and 0% to 15.9% for Neospora spp. Blood samples from a total of 440 horses, mules and donkeys from three different categories were sampled; urban horses, farm horses and sport horses. The samples was screened for antibodies using indirect fluorescent antibody test (IFAT), using a cut-off value of 1:16 for T. gondii and 1:50 for Neospora spp. The samples were tested in two-fold titrations until reaching end-point titer. Overall prevalence for T. gondii in the present study was 6.4% (28/440) and for Neospora spp. 4.5% (20/440), results that are among the lowest compared to prevalence studies made in other areas of Brazil. The end-point titers for T. gondii were in the lower end of the spectra, with 32.1% (9/28) of the positive samples having an end-point titer of 1:16 and the highest end-point titer being 1:1024. Analysis for Neospora spp. resulted high end-point titers, only 5.0% (1/20) of the seropositive individuals having an end-point titer of 1:50 and the highest titer being 1:2800. The prevalence on the basis of different determinants gave statistically significant difference in frequencies in several determinant groups. For T. gondii, the prevalence in sport horses was higher than in urban horses. The prevalence of Neospora spp. was higher in males than females, in urban horses compared to farm horses and the prevalence in the municipalities of both Santarém and Óbidos was significantly higher than in Brasil Novo. Additional research is necessary to determine whether these statistically significant differences are reflecting reality or if they are a consequence of the study design. More studies are also needed to be able to estimate the true prevalence in Pará and in Brazil in general. This knowledge is of importance when calculating the risk of meat from infected horses causing clinical disease in humans.